Etyczne problemy w działalności gospodarczej spółek kapitałowych w sporcie kwalifikowanym - Pawlak, Zbigniew; Smoleń, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2011)
This paper focuses on some ethical issues of companies operating in the field of competitive sports including in particular: limited liability vis-à-vis creditors of the companies that discontinued their activities, but were not subject to liquidation, nor bankruptcy petition has been filed; hampered recognisability of individual companies due to frequent changing of their names and names of teams participating in the tournaments; legal and financial status, rights and duties of contestants of these companies are underdefined; company identity is violated due to the pursuing of merger and acquisition strategy. It was decided that the above issues exemplify broader problems between labour and capital in the contemporary enterprise. Addressing of the above issues is a tough and complicated process, and sometimes simply impossible in the situation where sports have been recognised as equal sphere of business activities and where basic rules of market economy are respected also with reference to this sphere of life.